2014
DOI: 10.1177/107327481402100210
|View full text |Cite
|
Sign up to set email alerts
|

Separation Surgery for Spinal Metastases: Effect of Spinal Radiosurgery on Surgical Treatment Goals

Abstract: The combination of separation surgery and high-dose hypofractionated or single-fraction SRS results in high local tumor control at 1 year and is an effective palliative paradigm for this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
86
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(88 citation statements)
references
References 49 publications
0
86
0
2
Order By: Relevance
“…1,31,37,46,47,52,62,70,72,79,86,95 Risk stratification of patients preoperatively is important to optimize outcomes, 48,52,65,74,86,93,98 and prior studies have identified anatomical location, tumor size, tumor histology, extent of resection, surgical approaches, age, functional status, comorbidities, preoperative medication (steroid use, morphine), longer operative time, insurance status, early postoperative complications, and adjuvant chemotherapy and radiotherapy as factors associated with postoperative morbidity and mortality. 1,[18][19][20][21][22][23][24]39,41,42,44,48,51,52,56,58,66,69,78,92,99 Nevertheless, many of these previous publications were retrospective, institutional studies, 10,11,55,60,65,87,…”
mentioning
confidence: 99%
“…1,31,37,46,47,52,62,70,72,79,86,95 Risk stratification of patients preoperatively is important to optimize outcomes, 48,52,65,74,86,93,98 and prior studies have identified anatomical location, tumor size, tumor histology, extent of resection, surgical approaches, age, functional status, comorbidities, preoperative medication (steroid use, morphine), longer operative time, insurance status, early postoperative complications, and adjuvant chemotherapy and radiotherapy as factors associated with postoperative morbidity and mortality. 1,[18][19][20][21][22][23][24]39,41,42,44,48,51,52,56,58,66,69,78,92,99 Nevertheless, many of these previous publications were retrospective, institutional studies, 10,11,55,60,65,87,…”
mentioning
confidence: 99%
“…The median follow-up was 7.6 months (range 1.0-66.4 months). 20,21 The pain, functional, and neurological results of posterolateral decompression and stabilization had been analyzed and reported in an earlier publication.…”
mentioning
confidence: 99%
“…22,28 Unfortunately, these aims must be balanced against each other, with local control and functional preservation generally taking priority over systemic control in most acute presentations. In cases with a high degree of spinal cord compression, the most common surgical approach for the thoracic and lumbar spine involves a laminectomy with pedicle screw stabilization; 3,13,42 for the cervical spine, an anterior approach with vertebral column reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Once the patient recovers from surgery, SSRS is contoured to cover the surgical field, and all residual tumor receives adequate tumoricidal doses of radiation since the epidural disease likely to be underdosed has been surgically removed. 4,5,22,28 Laufer et al documented a 1-year cumulative incidence of local recurrence of only 4.1% when separation surgery was used in combination with hypofractionated SSRS (24)(25)(26)(27)(28)(29)(30) Gy divided into 3 fractions) and 9% when surgery was followed by highdose single-fraction SSRS (24 Gy). 21 Percutaneous procedures for tumor ablation are widely used with the intent of local tumor control, as in the treatment of visceral 2,41 and bone metastasis.…”
mentioning
confidence: 99%